Unconsciously triggered cognitive conflict influences perceptual choice in active and sedentary individuals - Jiang, Ruichen (Frontiers in Human Neuroscience, 2024)
Introduction People who regularly exercise and receive training perform better when actioning unconscious cognitive tasks. The information flow triggered by a single unconscious visual stimulus has been extensively investigated, but it remains unclear whether multiple unconscious visual stimuli interact. This study aimed to explore the relationship between three simultaneous subliminal arrow stimuli (pointing in same or different directions), focusing on how they interact with each other and the subsequent priming effect on the target arrow in active and sedentary groups. Methods We used a priming paradigm combining flanker task to test the hypothesis. A total of 42 participants were recruited. Of these, 22 constituted the active group and 20 constituted the sedentary group. Results Behavioral data results revealed that the main effects of group and prime-target compatibility were significant. In the neurophysiological data, prime-target compatibility significantly influenced the latency of PP1. The amplitude of TP1 and TN2 mainly influenced the prime-flanker congruency. The prime-flanker congruency and groups interacted when the prime-target showed sufficient compatibility. The prime-flanker congruency, and the prime-target compatibility considerably influenced the TP3 amplitude in the anterior central frontal region (CZ electrode point). Conclusion Event-related potentials revealed the interactions between conscious processing and subliminal conflict in the early stages of perceptual and attention processing (target-related P1 potential component). These results suggest that exercise is helpful for coping with unconscious cognitive conflict.